Implementation of Independent Curriculum in Science Subjects at Elementary School 1 Tanggulangin Central Lampung - Anjarwati, Sulis; Khoiriyah, Binti (Journal of Biological Science and Education, 2025)
Learning in schools always follow channel changes that occur, one of which is use continuous curriculum done evaluation in a way continuous in accordance with needs. Independent Learning Curriculum is current curriculum This used start level school aware until college high. Research objectives This For describe How implementation Independent Learning Curriculum in the Science Subject at SDN 1 Tanggulangin, Central Lampung. Research done in the year 2024/2025 academic semester odd semester . Primary data was obtained from the observation and interview process carried out together participant students and teachers. Supported with secondary data that is documentation activity learning.  The results of the study show that the implementation of the independent learning curriculum in the science subject at SDN 1 Tanggulangin, Central Lampung has been running well and optimally, as evidenced by various learning activities that have involved all students. In addition, the use of learning methods used in the independent curriculum has also been good. Activities learning done in accordance with stages conveyed in the  independent learning curriculum, start from preparation or planning, activities learning until evaluation . Activities science learning does not only done in the class but also outside class , activity  students become the main target so that students become more happy and excited follow learning.Keywords:   Implementation , Curriculum Independence , Science Subject